Pilot observational cohort study to determine whether waveform and flow traces from mechanical insufflation–exsufflation (MI-E) can be used to identify laryngeal responses to MI-E and thus optimise treatment algorithms in neuromuscular patients in a tertiary centre: a protocol description - Stephanie K Mansell; Swapna Mandal; Amar Shah; Francesca Gowing; Rhiannon Parry; Charlotte Greenfield; Yogesh Bhatt (BMJ Open Respiratory Research)
Introduction Patients with neuromuscular disease often have a weak and ineffective cough due to respiratory muscle weakness. One treatment option is mechanical insufflation–exsufflation (MI-E), also known as cough assist, which is known to increase cough strength. However, some patients have a laryngeal response to MI-E, which can make the treatment ineffective. Currently, the only method for assessing this is via nasal endoscopy while using MI-E. Some MI-E devices have onboard secure data (SD) cards, which allow the visualisation of waveforms. We hypothesise that the waveforms can be used to identify laryngeal responses to the MI-E.Methods and analysis Participants will complete baseline assessments of spirometry, peak cough flow and sniff nasal inspiratory pressure. A nasal endoscope will be used to visualise the larynx during simultaneous MI-E via a mask with a drilled hole. MI-E will be delivered by an experienced physiotherapist. Four cycles of MI-E at a range of prescriptions will be delivered. MI-E waveforms will be downloaded into Care Orchestrator Essence software (Philips, Murraysville). Data will be collected prospectively and reviewed in a descriptive context, providing trends and potential rationales describing the waveforms in comparison to the nasal endoscope videos.Ethics and dissemination This protocol has been reviewed by the East of England-Cambridge Central Research Ethics Committee, who have granted a favourable ethical opinion. The study opened to recruitment in January 2022 and aims to publish trial results in June 2024.Trial registration number NCT05189600.